African swine fever virus pA104R protein acts as a suppressor of type I interferon signaling - Chen, Qichao; Li, Liang; Guo, Shibang; Liu, Zhankui; Liu, Lixinjie; Tan, Chen; Chen, Huanchun; Wang, Xiangru (Frontiers in Microbiology, 2023)
This study evaluates the role of the late viral protein, pA104R, in African swine fever virus immunosuppression. ASFV-encoded pA104R is a putative histone-like protein that is highly conserved throughout different virulent and non-virulent isolates. Previous studies have demonstrated that pA104R plays a vital role in the ASFV replication cycle and is a potential target for antiviral therapy. Here, we demonstrated that pA104R is a potent antagonist of type 1 interferon signaling. IFN-stimulated response element activity and subsequent transcription of co-transfected and endogenous interferon-stimulated genes were attenuated by pA104R treatment in HEK-293T cells. Immunoprecipitation assay and reciprocal pull-down showed that pA104R does not interact directly with STAT1, STAT2, or IRF9. However, pA104R could inhibit IFN signaling by attenuating STAT1 phosphorylation, and we identified the critical amino acid residues (R/H69,72 and K/R92,94,97) involved through the targeted mutation functional assays. Although pA104R is a histone-like protein localized to the nucleus, it did not inhibit IFN signaling through its DNA-binding capacity. In addition, activation of the ISRE promoter by IRF9-Stat2(TA), a STAT1-independent pathway, was inhibited by pA104R. Further results revealed that both the transcriptional activation and recruitment of transcriptional stimulators by interferon-stimulated gene factor 3 were not impaired. Although we failed to determine a mechanism for pA104R-mediated IFN signaling inhibition other than attenuating the phosphorylation of STAT1, these results might imply a possible involvement of epigenetic modification by ASFV pA104R. Taken together, these findings support that pA104R is an antagonist of type I interferon signaling, which may interfere with multiple signaling pathways.